The value of serum zinc, copper, ceruloplasmin levels in patients with gastrointestinal tract cancers - Alper BOZ; Osman EVLİYAOĞLU and Mehmet YILDIRIM and Nazif ERKAN and Baysal KARACA (Turkish Journal of Gastroenterology, 2019)
-